Calcium chloride regulates cellular calcium metabolism during the postharvest senescence of ripe passion fruit - Ting Wei; Hai Wang; Shurou Chen; Jing Li; Xia Li; Ming Xin; Xinhong Dong; Hock Eng Khoo (Acta Scientiarum Polonorum: Hortorum Cultus)
The impact of calcium chloride (CaCl2) treatment and water soaking on the postharvest senescence of the ripened passion fruit was investigated. The physicochemical indexes including weight loss, color change, membrane permeability, malondialdehyde (MDA) content, total phenolics, flavonoids, ascorbic acid content, peroxidase (POD), polyphenol oxidase (PPO), and distinct forms of calcium of the fruit were determined using the established methods for analysis. The correlation and principal component analyses were also conducted on the experimental data. The results demonstrated that the calcium ions were effective in maintaining the appearance and color of the fruit peel, enhancing its antioxidant capacity, and regulating its nutrient content. This treatment significantly increased the calcium content of the passion fruit peels, extending the fruit’s freshness beyond four days. The correlation analysis revealed a positive correlation between the mass loss rate of the passion fruit and the majority of the physicochemical properties examined. The findings indicated that the calcium chloride treatment could effectively maintain fruit storage quality and prolong the shelf life of postharvest passion fruit by several days. It seems reasonable to posit that calcium chloride will become the preferred method for postharvest fruit preservation in the near future.